Corporate social responsibility performance, financial distress and firm life cycle: evidence from Australia. (18th May 2017) - Al‐Hadi, Ahmed; Chatterjee, Bikram; Yaftian, Ali; Taylor, Grantley; Monzur Hasan, Mostafa
Abstract: This study examines the association between corporate social responsibility (CSR) performance and financial distress and additionally the moderating impact of firm life cycle stages on that association. Based on a sample of 651 publicly listed Australian firm‐years' data covering the 2007–2013 period, our regression results show that positive CSR activity significantly reduces financial distress of the firm. In addition, the negative association between positive CSR performance and financial distress is more pronounced for firms in mature life cycle stages. Our results are robust to alternative proxy measures of financial distress, CSR performance and life cycle stages.